MENINGKATKAN KEMAMPUAN BELAJAR MATEMATIKA DENGAN MODEL PEMBELAJARAN PQ4R - Pulungan, Lilik Hidayat (Hijri, 2021)
The purpose of this study was to determine student learning outcomes and to determine student activity after implementing the PQ4R learning model for VII students of SMP Muhammadiyah 1 Medan with material in algebraic forms. The research instrument used was a test in the form of three types of descriptions, where each test consisted of 5 questions, observation, evaluation and class action. As subjects in this study were all class VII students of SMP Muhammadiyah 1 Medan, totaling 36 people. The cause of students' difficulties in learning integers is because students do not master the concept of integers and students do not master the material provided by the teacher. To overcome these difficulties, efforts are needed to improve student learning outcomes by applying learning methods, namely the PQ4R model and through group study. The data obtained from student learning outcomes before learning was carried out reached 14.28% and the student's incompleteness score was 85.72%, then it increased in cycle I to 60% of the value of incompleteness was 40% and in cycle II it increased to 88.57% while students who did not complete reached 11.43%. or if viewed from the level of learning completeness then the initial test results obtained 30 people who scored below completeness and in the first cycle there were 14 people then in the second cycle there were 4 people. This shows that after being taught with the PQ4R model on the subject of algebraic forms the learning outcomes of mathematics and student activity have increased from cycle I to cycle II.Keywords:PQ4R model, ability to learn mathematics